Comments on "Efficiency analysis of novel Liquid Organic Hydrogen Carrier technology and comparison with high pressure storage pathway" [Int. J. Hydrogen Energy 41 (2016) 18062–18071]. (23rd November 2017) - Yang, Ming; Sun, Yanlong; Cheng, Hansong
Abstract: We present critical comments on a recent article entitled "Efficiency analysis of novel Liquid Organic Hydrogen Carrier technology and comparison with high pressure storage pathway" (Int. J. Hydrogen Energy 41, 18062, 2016). A careful analysis on the energy efficiency of the hydrogen storage methods based on compressed gas and liquid organic hydrogen carrier technologies is of fundamental importance for making a rational choice of storage techniques to be used for onboard automotive applications.